1996
DOI: 10.1136/jcp.49.11.889
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of cutaneous tuberculosis in biopsy specimens by PCR and southern blotting.

Abstract: Aims-To evaluate the use of a gene amplification and hybridisation method for detecting mycobacterial nucleic acid as a possible diagnostic method for cutaneous tuberculosis infection. Methods-Biopsy specimens from 20 patients with various skin conditions of possible tuberculous aetiology were studied. Six patients had ulcerative nodules, seven lupiform lesions, two non-necrotic granulomas, one scrofulous lichen, one impetigo, one erythematosus lesions, one warty lesions, and one suspected tuberculous lipoma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…They were confirmed by rapid tests. Viswanathan et al,15 reported a similar incidence of 13.7% in their study, which was similar to that reported by Quiros et al (20%) 16. While TB prevalence has remained stable, the incidence continues to rise, especially in developing countries.…”
Section: Discussionsupporting
confidence: 83%
“…They were confirmed by rapid tests. Viswanathan et al,15 reported a similar incidence of 13.7% in their study, which was similar to that reported by Quiros et al (20%) 16. While TB prevalence has remained stable, the incidence continues to rise, especially in developing countries.…”
Section: Discussionsupporting
confidence: 83%
“…Two sections from each biopsy specimen were treated and submitted for PCR amplification as previously described (12,13). Briefly, after xilene treatment and proteolitic digestion in 200 µl of buffer, 20 µl of samples were incubated in a PCR buffer (10 nmol (5′-TGG-TCC-GGT-TCA-TAC-TCG-GGC-TGG-3′) primers make up to 60 µl of total volume for 5 minutes at 95°C (denaturation) and subjected to PCR amplification for 40 cycles of 94°C and 70°C (1 minute at each temperature).…”
Section: Pcr Proceduresmentioning
confidence: 99%
“…Briefly, samples were transferred to Hyband N + nylon fillers (Amersham, Little Chalfont, UK) incubated with 5 × SSC, 5 × Denhardt's solution, 0,5% of SDS, and 100 ngr/ml denatured salmon sperm DNA for one hr at 58°C, them hybridized for 18 hr at 58°C with a p32 5′-end labelled internal probe as previously described (14). All chemical reagents were purchased from Sigma Diagnostics (St. Louis, MO).…”
Section: Pcr Proceduresmentioning
confidence: 99%
“…A study showed PCR to be more sensitive than Ziehl-Nielsen staining (85% vs 30%), and than culture ( 85% vs 60%). PCR showed also to be more specific since all PCR negative samples were also negative when culture or stained by Ziehl-Nielsen [12]. Therefore modern tests to detect tuberculosis, such as genetic detection by means of PCR, currently allow us to obtain an early and precise diagnosis and to ensure an early oriented medical treatment.…”
Section: Scrofuloderma Induced By Surgical Drainage In a Joint Tubercmentioning
confidence: 97%